2017
DOI: 10.1002/jor.23746
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of developmental spinal stenosis: A genome‐wide association study

Abstract: Our study aimed to identify possible single nucleotide polymorphisms (SNPs) via a genome-wide association study (GWAS) approach and a candidate gene platform that were associated with lumbar developmental spinal stenosis (DSS). Southern Chinese population-based study volunteers were assessed (age range: 18-55 years). DSS was defined as the anteroposterior bony spinal canal diameter on T1-weighted axial MRI of L1 to S1. Genotyping was performed using the Illumina HumanOmniZhongHua-8 BeadChip. Using the canal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…For the past 20 years, the spine field has seen a surge in studies addressing human genetics and the ability to identify millions of individual single nucleotide polymorphisms in relation to various imaging and/or clinical phenotypes. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] In fact, we have been witnesses to the rise of transcriptomics, proteomics, microbiome, metabolomics and a plethora of other big data "omics" platforms along with their applications toward spine disease. Even the phenotyping of disc cells and other spinal structures, the exponential rise of molecular and biomarker epidemiology, and motion kinematic and analyses further lend to multidimensional big data considerations and integration between different disciplines.…”
Section: Applications Of Deep Learningmentioning
confidence: 99%
“…For the past 20 years, the spine field has seen a surge in studies addressing human genetics and the ability to identify millions of individual single nucleotide polymorphisms in relation to various imaging and/or clinical phenotypes. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] In fact, we have been witnesses to the rise of transcriptomics, proteomics, microbiome, metabolomics and a plethora of other big data "omics" platforms along with their applications toward spine disease. Even the phenotyping of disc cells and other spinal structures, the exponential rise of molecular and biomarker epidemiology, and motion kinematic and analyses further lend to multidimensional big data considerations and integration between different disciplines.…”
Section: Applications Of Deep Learningmentioning
confidence: 99%
“…Several studies have identified candidate genes associated with lumbar disc degeneration. Jason et al performed a genome-wide association study and identified multiple SNPs suggesting a multifactorial basis for DLSS [16]. In other work, the HLA-DRB1 genotype increased the risk of developing pain after surgery or lumbar disc herniation [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, significant association was only observed in spinal stenosis subgroup, but not in LDH subgroup. This discrepancy could be explained by the fact that LDD has a complex and heterogeneous pathogenesis [29][30][31] . Therefore, from our results, we postulated that these variants may exert more influence in the advanced stages of LDD development in Chinese population.…”
Section: Discussionmentioning
confidence: 99%